Estrategias de mejoramiento de frijol para un sistema asociado con maiz, en el Valle Sagrado, Cusco-Peru - Ortíz Arriola, V.; Maître, Adrian (International Center for Tropical Agriculture, 1989)
The improvement strategy of climbing bean in Cusco should take into account the importance of maize as a crop. In a recent study in 2 maize-growing communities of Valle Sagrado, 75 and 88 percent of the farmers considered beans as the main crop; however, only 57 and 22 percent of the maize-growing area was planted to beans. Furthermore, farmers usually plant beans at low densities, partly due to the high degree of competition with maize. This practice causes low bean yields (300-500 kg/ha). Considering these data, and to take advantage of the large areas planted to maize in Valle Sagrado and other areas, the improvement strategy has consisted in developing bean lines apt for associated cropping with maize. The new lines allow maize to maintain its yield level, while increasing bean production/ha. Using this strategy and on the basis of previous evaluations, 15 promising bean lines were selected at the Taray Exptl. Station for the 1988/89 cropping season. Of these, outstanding lines were ZAV 8382 (1354 kg beans and 7667 kg maize/ha), ZAV 8397 (1354 kg beans and 7395 kg maize/ha), and ZAV 8398 (1052 kg beans and 8156 kg maize/ha), compared with the local check Amarillo Gigante (1350 kg beans and 4500 kg maize/ha). The local check, due to its IVb growth habit (very aggressive), reduced maize yields significantly; the new lines, however, overcome this disadvantage, all being of growth habit IVa (less aggressive). (AS- CIAT)